Replacement of the European wheat yellow rust population by new races from the centre of diversity in the near‐Himalayan region. (20th July 2015) - Hovmøller, M. S.; Walter, S.; Bayles, R. A.; Hubbard, A.; Flath, K.; Sommerfeldt, N.; Leconte, M.; Czembor, P.; Rodriguez‐Algaba, J.; Thach, T.; Hansen, J. G.; Lassen, P.; et al.
Abstract : Isolates of recently spreading races of yellow rust from wheat and triticale in Europe were analysed using virulence phenotypic data of 2605 isolates sampled in 12 countries between 2000 and 2014. A subset of 239 isolates was investigated by microsatellite markers. At least three races of non‐European origin, termed 'Warrior', 'Kranich' and 'Triticale aggressive', were identified in the post‐2011 population. The Warrior race was already present in high frequencies in the first year of detection in most European countries and to a large extent it replaced the pre‐2011 European population. In contrast, the two other exotic races were localized to certain regions and/or crop type. The presence already of at least six multilocus genotypes of the Warrior race and five genotypes of the Kranich race in the first year of detection and across large areas is consistent with a hypothesis of aerial spread from genetically diverse source populations. A comparison with reference isolates sampled from six continents suggested that the Warrior and Kranich races originated from sexually recombining populations in the centre of diversity of the yellow rust fungus in the near‐Himalayan region of Asia. However, the Triticale aggressive race was most similar to populations in the Middle East/Central Asia. The study illustrated the potential role of sexual Puccinia striiformis populations as a reservoir for new races replacing distant clonal populations.